Use of exergaming and its effects on the physical health of patients diagnosed with cancer: an integrative review (Fisioterapia e Pesquisa, 2020)
This study aimed to search for records with significant differences regarding the physical health of cancer patients when practicing exergaming. The integrative literature review was used as method with the keywords “Physiotherapy,” “Virtual Reality,” “Wii,” “Exergames” and “Cancer,” in Portuguese and English, in the following databases: PubMed, Science Direct, Medline, Scopus, Lilacs, SciELO, PEDro, Cochrane and Capes Journals. The inclusion criteria were studies that used exergaming in clinical treatments and presented differences on the physical health of patients diagnosed with cancer, of both sexes, of all ages and types of cancer, published in the last 10 years, in any language. Of the 3,172 articles found, only nine were included; they evaluated physical performance, sedentary lifestyle, upper limbs functionality, lower limbs muscle strengt